2006
DOI: 10.2174/157340906778226454
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Free Energy Calculations with a Combination of Molecular Mechanics and Continuum Models

Abstract: Abstract:Recently, the combination of state-of-the-art molecular mechanical force fields with continuum solvation models enables us to make relatively accurate predictions of both structures and free energies for macromolecules from molecular dynamics trajectories. The first part of this review is focused on the history and basic theory of free energy calculations based on physically effective energy functions. The second part illustrates the applications of free energy calculations on many biological systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
269
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(273 citation statements)
references
References 53 publications
3
269
1
Order By: Relevance
“…This result is in agreement with the previous studies which showed that MM/GBSA method is often useful to refine the binding scores resulted from docking-based virtual screening [15]. Nevertheless, a better conformational sampling for MM/GBSA method should be able to improve the accuracy of binding energy calculation.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with the previous studies which showed that MM/GBSA method is often useful to refine the binding scores resulted from docking-based virtual screening [15]. Nevertheless, a better conformational sampling for MM/GBSA method should be able to improve the accuracy of binding energy calculation.…”
Section: Discussionsupporting
confidence: 92%
“…39 Binding free energy approaches like MM/PBSA and MM/GBSA are computationally more efficient 36,44,45 than the theoretically rigorous approaches such as thermodynamic integration 46 and free energy perturbation. [47][48][49] In this study, the binding free energies were estimated using mmpbsa program in AMBER.…”
Section: Resultsmentioning
confidence: 99%
“…Each of the TPO 201-500 -ATD complexes was subjected to Molecular Dynamics simulation to study its stabilizing properties. In addition, PoissonBoltzmann and generalized Born and surface area continuum solvation (MM/PBSA and MM/GBSA) [47][48][49][50][51] techniques were endorsed to calculate binding free energies of MMZ and PTU to TPO 201-500 . PBTOT for TPO 201-500 -MMZ and TPO 201-500 -PTU was -11.05 and -14.02 kcal mol-1 while GBTOT for TPO 201-500 -MMZ and TPO 201-500 -PTU was found -9.43 and -15.47 kcal mol-1 respectively, which put forth the inhibitors to have high affinity to TPO 201-500 in the dynamic system.…”
Section: Introductionmentioning
confidence: 99%